External Environmental Factors and Failure of Small and Medium Enterprises in Kano Metropolis - Abubakar, Salihu; Junaidu, Abubakar Sambo (Asian Journal of Economics and Empirical Research, 2019)
This study examines the relationship between external environmental factors and failure of SMEs in Kano metropolis, using samples of failed SMEs in Kano metropolis. Questionnaire was used to collect primary data from the sampled failed SMEs using snow ball method. The data was analyzed using multiple regression technique and descriptive statistics in order to establish the significance of the estimated relationships. The outcome reveals that external environmental factors have significant impact on the failure of SMEs in Kano metropolis, and inadequate infrastructure (II) is the major contributing factor to the failure of SMEs in the Kano; followed by market competition (MC), market demographics (MD), and financial inadequacy (FI). In order to reduce SMEs failure and achieve significant positive contribution of SMEs sub-sector to the economic development of the state, the study recommends that government and relevant stakeholders should create an enabling business environment with adequate infrastructures, fear competition, sound market places and financial support.